Census tract based income level and lipid levels in urban pediatric primary care: a retrospective study. Issue 1 (December 2016) - Martinez, Enid; Forbes, Peter; O'Brien, Sharon; de Ferranti, Sarah
Abstract Background Lower socioeconomic status has been associated with adverse lipid levels in adult populations. Childhood dyslipidemia is a risk factor for future cardiovascular disease. However, studies examining relationships between socioeconomic indicators and lipid levels in children are limited. To examine the relationship between income level and lipid levels in childhood. Methods We conducted a retrospective chart review of primary care patients, ages 2 to 18 years, who had lipid levels drawn at two large pediatric practices in Boston, MA between August 01, 2008 and August 31, 2010. Income level was determined using geocoding census tract data. Analysis was performed using t-test, Anova and Spearman correlation coefficients. BMI percentile, age, sex, race/ethnicity, and site were adjusted for on multivariate analyses. Results Reviewing 930 charts of patients with measured lipid levels, 730 had a valid address, no previously diagnosed lipid disorder and met other study eligibility criteria. Mean total cholesterol level did not vary by income level (low 155.5 mg/dl ±26.9, moderate 153.5 mg/dl ±30.4, middle 155.3 mg/dl ±26.6 and high income 155.5 mg/dl ±27.9;p  = .87) on multivariate analysis. Income level was not related to LDL, HDL, or triglycerides. Conclusions In this analysis of children cared for in two urban pediatric primary practices, there was no association between income level determined by census tract and lipid levels in childhood. If confirmed in prospective investigations in other geographical locations, income level may not be a key driver of childhood lipid levels.